Aplikasi Instagram sebagai Media Komunikasi Pemasaran Online Shop di @novashoptakengon.id - Suknah Suknah; Viana Safrida Harahap; Subhan AB; Darmila Yanti (Lembaga Pengembangan Kinerja Dosen, 2023)
The objectives of this research are 1) To find out how the Instagram application is used as an online shop marketing communication medium, 2) To find out the obstacles to the Instagram application being used as an online shop marketing communication medium. The location of this research was carried out at the Novashoptakengon.id mini online shop located in Uning Village, Pegasing District, Central Aceh Regency with the number of informants being 1 owner, 4 resellers and 1 consumer of the Novashoptakengon.id Online Shop. Data collection used in this research is interviews and observations with owners, resellers and consumers. Data analysis techniques consist of data collection, data reduction, data presentation and drawing conclusions. The results of the research are marketing communications carried out via Instagram media which are used by online shop owners through promotions on the Instagram application. Of the various supporting features built into Instagram, the features most frequently used are the Instagram story photo upload and Story Highlights features. In the Instastory feature, Mrs. Nova Sri Rezeki uses it to inform about the latest products and shop situations every day. Meanwhile, to upload photos, Mrs. Nova Sri Rezeki uses it to post new products with attractive layouts. Story Highlights are used to provide important information such as how to order online, shop location instructions, shopee address and others. This feature used is considered very effective and helpful in the product promotion process, because it can convey messages directly to consumers. By utilizing the number of followers which has reached 4,934 thousand, it will make it easier to promote products. The problem with the Instagram application being that it is used as a marketing communication medium for online shops is competition between other online shops, so that the owner must be diligent in posting photos or videos so that his products can be seen by consumers, otherwise he will be at risk of losing consumers. People will switch to other online shops.